2015
DOI: 10.3233/rnn-140439
|View full text |Cite
|
Sign up to set email alerts
|

Early hyaluronate injection improves quality of life but not neural recovery in unilateral vocal fold paralysis: An open-label randomized controlled study

Abstract: Purpose: To investigate the neurologic and functional effect of intracordal hyaluronate injections in acute unilateral vocal fold paralysis (UVFP) in a randomized controlled trial. Methods:In this open-label, randomized controlled study, 29 patients with UVFP were recruited within 6 months of their first outpatient visit and were randomized to receive either single hyaluronate injection (HI group) or conservative management (CM group). Quantitative laryngeal electromyography, videolaryngostroboscopy, UVFP-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 20 publications
3
32
0
1
Order By: Relevance
“…Our findings are consistent with prior studies that have shown a benefit to early-injection laryngoplasty in patients with UVFP, including improvements in short-term quality of life, 21,22 voice quality, 23 and acoustic parameters. 24 Furthermore, others also have theorized that early-injection laryngoplasty would lead to a decrease in the rate of future thyroplasty based on their own retrospective studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with prior studies that have shown a benefit to early-injection laryngoplasty in patients with UVFP, including improvements in short-term quality of life, 21,22 voice quality, 23 and acoustic parameters. 24 Furthermore, others also have theorized that early-injection laryngoplasty would lead to a decrease in the rate of future thyroplasty based on their own retrospective studies.…”
Section: Discussionsupporting
confidence: 92%
“…This corroborates recent findings from the Pei et al open-label randomized trial in which early hyaluronate injection did not improve nerve regeneration, but it made a significant impact on patient quality of life. 19 Several previous studies have considered this relationship. Yung et al found that 26% (5/19) of patients injected versus 66% (23/35) of patients not injected ultimately required definitive type I laryngoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The study patients were free to choose the treatment options as observation or underwent hyaluronate injection laryngoplasty (HIL) for their initial symptoms, as described previously . For HIL, patients were seated upright without sedation, and lidocaine spray was administered into their mouth and nose until numbness was experienced.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative LEMG that measures the turn frequency has recently provided additional information on laryngeal neuromuscular activity . Evaluating TA‐LCA muscle complex activity using quantitative LEMG at multiple time points can objectively evaluate the recovery …”
Section: Introductionmentioning
confidence: 99%